Ideas Organization In Student Writing: Essay Assessments In EFL Classroom - Rizka Maulina Wulandari; A’thi Fauzani Wisudawati; Muhammad Isa (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Ideas organization is an important part of most good essay writing theory. A very common problem with long texts is poor organization. An essay has a few components on it such as thesis statement, unity, organization, body, conclusion, paragraph, transition, and effective sentence. This study focuses on the organization of ideas in the fifth semester essay writing at the English Department of Muhammadiyah Malang University. The method used in this study was a descriptive qualitative research. The researcher selected class A of fifth-semester students from the English Department of Muhammadiyah Malang University as the respondent. In addition, the data of this study were articles or compositions of essays and student statements obtained from interviews. The results showed that nearly 75% of students in the fifth semester of the A class of English Department of Muhammadiyah Malang University found a way to organize their ideas when writing an essay. As a result, 25% of students had difficulty organizing their thoughts and also indicated that they knew the problems they were facing and how to solve them by presenting appropriate solutions. These results have implications for writing theories and writing practice.